Proceedings of the 21st International Conference on World Wide Web 2012
DOI: 10.1145/2187836.2187867
|View full text |Cite
|
Sign up to set email alerts
|

Economics of BitTorrent communities

Abstract: Over the years, private file-sharing communities built on the BitTorrent protocol have developed their own policies and mechanisms for motivating members to share content and contribute resources. By requiring members to maintain a minimum ratio between uploads and downloads, private communities effectively establish credit systems, and with them full-fledged economies. We report on a half-year-long measurement study of DIME -a community for sharing live concert recordings -that sheds light on the economic for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
2

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 15 publications
0
21
2
Order By: Relevance
“…However, many measurement studies [5], [12] show that the popularity of a file decreases quickly after it is first published. In this section, we analyze the effects of SRE and evaluate our proposed strategies under dynamic file popularity.…”
Section: Dynamic File Popularitymentioning
confidence: 99%
See 1 more Smart Citation
“…However, many measurement studies [5], [12] show that the popularity of a file decreases quickly after it is first published. In this section, we analyze the effects of SRE and evaluate our proposed strategies under dynamic file popularity.…”
Section: Dynamic File Popularitymentioning
confidence: 99%
“…However, they did not propose strategies to solve the problem. Kash et al [12] demonstrate that in a private community named DIME, after a period of freeleech, there are more download activities in the community. This is consistent with our theoretical result that during a pre-crunch state, injecting credit will increase the system throughput.…”
Section: Related Workmentioning
confidence: 99%
“…Increase in download activity as the aftermath of freeleech period has been demonstrated in [14]. The study is based on real-world measurement of the DIME private BitTorrent community.…”
Section: Related Workmentioning
confidence: 99%
“…Although we use the terminology 'initial amount', the different scenarios we study here resemble actual situations in real-life BitTorrent communities after so-called freeleech period [14]. During these periods peers do not need to spend credit for download.…”
Section: Effect Of Initial Credit Amount and Distributionmentioning
confidence: 99%
“…On the other hand, in open BitTorrent communities (represented by the Synthetic graphs), where no explicit rules are (and could be) applied regarding the seeding, it is better if each seeder uploads in one swarm only. According to Kash et al [25], observation of a private BitTorrent community revealed that many peers are seeding in multiple torrents. While it is practically impossible to find relevant measurements regarding the open BitTorrent, Cuevas et al [26] shows that, on average, a regular publisher (user who injects new content into the BitTorrent network) seeds concurrently only in one torrent.…”
Section: One Swarm Per Seedermentioning
confidence: 99%